Evaluating Renewable Groundwater Stress with GRACE Data in Greece. Issue 3 (22nd September 2017) - Gemitzi, Alexandra; Lakshmi, Venkat
Abstract: Groundwater is a resilient water source and its importance is even greater in periods of drought. Areas such as the Mediterranean where adverse climate change effects are expected are bell‐weather locations for groundwater depletion and are of considerable interest. The present study evaluates renewable groundwater stress (RGS) as the ratio of groundwater use to groundwater availability, quantifying use as the trend in gravity recovery and climate experiment‐derived (GRACE) subsurface anomalies (ΔGWtrend ) and renewable groundwater availability as mean annual recharge. Estimates for mean annual recharge for the various regions in Greece have been derived using numerical models. Our results highlight two RGS regimes in Greece (variable stress and unstressed) of the four characteristic stress regimes, that is, overstressed, variable stress, human‐dominated stress, and unstressed, defined as a function of the sign of use and the sign of groundwater availability (positive or negative). Variable stress areas are found in Central Greece (Thessaly region), where intensive agriculture results in negative ΔGWtrend values combined with positive mean annual recharge rates. RGS values range from −0.05 to 0, indicating a low impact area. Within this region, adverse effects of groundwater overexploitation are already evident based on the negative GRACE anomalies; however, recharge is still positive, mitigating the effects of over‐pumping. The rest of Greek aquifers fall within the unstressed category, with RGS values from 0.02 to 0.05, indicating that the rate of use is less than the natural recharge rate. Abstract : Article impact statement : GRACE‐derived renewable groundwater stress was found to be an efficient way of highlighting areas facing quantitative groundwater stress.